Development, planning and participation in New Brunswick - Young, R; Young, Robert Andrew (1980)
﻿ This is a study of political change in a small Canadian province. At its centre is the tension between rational plans for economic development and political demands grounded in existing attitudes and interests. This must be resolved for plans to be realised in new behaviour, and some elites will extend participation in planning, (which stimulates, informs, and commits participants to implement them), while minimising its effective impact on plans. In 1940, New Brunswick was under-developed and typically peripheral, with regional political structures that coincided with economic clienteles based in primary production. Its political evolution is traced primarily through detailed studies of three exercises in development planning. These rely on newspapers, interviews, government documents both published and unpublished, and archival material. Public participation was first conjoined with planning for post-WWII reconstruction. State spending, however, continued to support established regional elites. In the 1950s, New Brunswick's Electric Power Commission planned infrastructure for foreign investors in heavy industry. This case illustrates expertise's growing influence, the importance of implicit organisational goals, and the accommodation of interests by active organisations: these were relevant to the state as a whole after power was centralised in the 1960s. Then, a comprehensive plan for one region was designed, but the extensive participatory structures implanted facilitated resistance to an imposed plan rather than its implementation. As development proceeds, ineffective participation in planning - involvement - becomes insufficient to generate consent. It is shown that individuals' political action is unlikely to be effective, so plans must be formulated, and consent secured, through interest-organisations. Provincial interest groups are explored, through their incorporation records and a sample survey. Their relations with the state (itself treated as a purposeful organisation) are analysed. It is found that the working classes, rural inhabitants, and francophones are organisationally under-represented and lack an effective part in planning. The implications of their disaffection are briefly discussed.